Enabling cyber–physical systems with machine–to–machine technologies. (30th July 2013) - Wan, Jiafu; Yan, Hehua; Liu, Qiang; Zhou, Keliang; Lu, Rongshuang; Li, Di
In recent years, Cyber–Physical Systems (CPS) has emerged as a promising direction to enrich the interactions between physical and virtual worlds. While Machine–to–Machine (M2M), Wireless Sensor Networks (WSNs) and CPS are quite similar in many networking aspects, there are still some major differences. In this paper, we first review several concepts and terms, including M2M, WSNs, CPS and Internet of Things (IoT). Then, we conduct a case study exemplified by home M2M networks, and outline the further research proposals of M2M communications. On this basis, a case of CPS, Human–Cyber–Physical System (HCPS) to achieve system safety and efficiency for connected vehicles, is proposed, and the research proposals and challenges for HCPS are summarised. Finally, we carry out a comparison of M2M and CPS to demonstrate how M2M systems with the capabilities of decision–making and real–time control can be upgraded to CPS.